Dilemmas of Fatwas Freedom in Morocco: Between Diversity of Religious Perspectives or National Stability - Ashufah, Abdul Hayyaqdhan; Abderrahmane, Kchich; Hamzah, Alya Aulia Rachman; Aatifi, Omayma; Azamy, Muhammad Mumtaz (Universitas Islam Negeri Alauddin Makassar, 2025)
In Morocco, fatwa authority has been strictly centralized through the Al-Majlis al-‘Ilmi al-A‘la under the King’s religious leadership as Amir al-Mu’minin. This system seeks to preserve the unity of the Maliki school and maintain national stability, yet it simultaneously raises dilemmas concerning the freedom of fatwas and the diversity of religious perspectives. This study analyzes the construction of Morocco’s fatwa authority and examines society’s responses to this centralized framework. Employing a descriptive-qualitative method with a socio-legal Islamic approach, the research draws on literature review and document analysis, utilizing primary sources such as official fatwas issued by Moroccan religious institutions and secondary sources including academic articles and digital media. The findings show that fatwas in Morocco serve not only as religious guidance but also as instruments of state legitimacy in shaping and regulating public religious discourse. At the same time, certain segments of society express resistance by turning to independent scholars and digital platforms, thereby challenging the state’s monopoly over religious interpretation. The article contributes to academic discourse by mapping the dynamics between state and religious authority in the Moroccan context and highlighting the epistemological challenges posed by digitalization and social transformation. Ultimately, this study underscores the tension between institutional stability and societal pluralism, offering insights into how fatwas function as both theological and political tools in contemporary Islamic law.